2011
DOI: 10.1080/00224065.2011.11917867
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Control Charts for Standard Deviation with Estimated Parameters

Abstract: Design and analysis of control charts for standard deviation with estimated parametersSchoonhoven, M.; Riaz, M.; Does, R.J.M.M. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…An unbiased estimator of σ is given by Sc/d(c,n,k), where d ∗ ( c , n , k ) is the normalizing constant. In our study, we use the corrected normalizing constants given in Schoonhoven et al …”
Section: Proposed Phase I Estimatorsmentioning
confidence: 99%
“…An unbiased estimator of σ is given by Sc/d(c,n,k), where d ∗ ( c , n , k ) is the normalizing constant. In our study, we use the corrected normalizing constants given in Schoonhoven et al …”
Section: Proposed Phase I Estimatorsmentioning
confidence: 99%
“…The advantage of this estimator is that it is less sensitive to outliers than R (cf. Schoonhoven et al 2011). The resulting estimator is denoted by MD s .…”
Section: Estimators Of the Standard Deviationmentioning
confidence: 99%
“…Additionally, we look at an adaptive trimmer based on the mean deviation from the median, a statistic more resistant to diffuse outliers (cf. Schoonhoven, Riaz, and Does 2011). For diffuse outliers, we think that a control chart for individual observations would detect outliers more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…What remains is the determination of the factors U II and L II in order to obtain the desirable in-control performance. Schoonhoven et al (2011) presented a formula for U II and L II of the Phase II standard deviation control chart based on the pooled mean of the sample standard deviations,S S. They tested this formula for charts derived from a broad range of Phase I estimators and concluded that the formula is suitable when the variance of the estimator is close to the variance ofS S. Subsequently, Schoonhoven and Does (2013) showed that the variance of the estimator given in [5] is close toS S. Hence, the formula presented by Schoonhoven et al (2011) can also be applied in the procedure discussed here. This is a nice result because the formula is a plug-in so no simulations are required to obtain the constants.…”
Section: Phase IImentioning
confidence: 97%